Profile of the Problem-Based Learning Model Assisted by ELTRA to Strengthen Students’ Problem-Solving Skills in Support of SDG 4: Quality Education - Nurul Muawiyah; Elvia Reza Lutfiani; Nofri Hidayatin; Siska Agustin Sha Hareni; Dhea Wanda Irani; Binar Kurnia Prahani (Journal of Psychology and Culture Behavior in SDGs, 2026)
Objective: This study aims to analysed senior high school students’ physics problem-solving skills on the topic of Light Waves as a basis for implementing a Problem-Based Learning (PBL) model assisted by a digital book (ELTRA) in supporting SDG 4: Quality Education. Method: The research employed a qualitative descriptive design using a preliminary survey approach. Data were collected through problem-based essay tests, student response questionnaires, and teacher interviews. The participants were 104 eleventh-grade students from three science classes at MAN 2 Gresik. Students’ test results were analysed using qualitative descriptive analysis based on five indicators of problem-solving skills: visualizing the problem, describing physics concepts, planning solutions, executing plans, and evaluating results. Results: The findings revealed that most students demonstrated low problem-solving skills. A total of 102 students were categorized at a low level (scores 0–40), only two students reached the moderate category (scores 41–70), and none achieved a high level (scores 71–100). These results indicate that students experience difficulties in applying structured problem-solving steps, particularly in planning and executing solutions. Novelty: This study provides an empirical problem-solving profile as a foundational need analysis for developing a PBL model integrated with an ELTRA digital book, specifically designed to support structured physics problem-solving skills and align physics learning innovation with the objectives of SDG 4.